1878 Miss. Laws 176, ch. 46, § 4. - (:unkn) unknown (General Publisher, 1878)
[A]ny student of any university, college or school, who shall carry concealed, in whole or in part, any weapon of the kind or description in the first section of this Act described, or any teacher, instructor, or professor who shall, knowingly, suffer or permit any such weapon to be carried by any student or pupil, shall be deemed guilty of a misdemeanor, and, on conviction, be fined not exceeding three hundred dollars, and if the fine and costs are not paid, condemned to hard labor under the direction of the board of supervisors or of the court.
--
Keywords: SENSITIVE PLACES